2021
DOI: 10.5114/aoms/100600
|View full text |Cite
|
Sign up to set email alerts
|

The Association between Micro-RNA Gene Polymorphisms and Development of Hepatocellular Carcinoma in Egyptian Patients

Abstract: IntroductionThe development and progression of hepatocellular carcinoma (HCC) is a multistage process involving the deregulation of genes that are crucial to cellular processes. Multiple risk factors are correlated with HCC. MicroRNA is differentially expressed in development of different types of malignancies, including hepatic malignancy. Single nucleotide polymorphisms (SNPs) are the most common sequence variation in human genome. SNPs in miRNAs may affect transcription, processing or target recognition and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 29 publications
(25 reference statements)
0
5
0
Order By: Relevance
“…(1) The patients in our study were part of a single-center study. (2) We had some missing data such as iron or vitamin B 12 deficiency and other diseases that may affect RCDW values. (3) We analyzed all hospitalized patients together despite their etiologies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…(1) The patients in our study were part of a single-center study. (2) We had some missing data such as iron or vitamin B 12 deficiency and other diseases that may affect RCDW values. (3) We analyzed all hospitalized patients together despite their etiologies.…”
Section: Discussionmentioning
confidence: 99%
“…Most causes of morbidity and mortality in chronic hepatitis patients are related to liver fibrosis, liver cirrhosis and portal hypertension [1][2][3]. Hepatitis C virus (HCV) infection is a severe public health issue that affects 170 million individuals globally [4,5].…”
Section: Introductionmentioning
confidence: 99%
“…Consequently, genetic differences in miRNAs have been related to the development of HCCs. Numerous studies have shown that susceptibility genes and abnormal gene expression are risk factors for HCC (77).…”
Section: Gene Polymorphismmentioning
confidence: 99%
“…At least 12 kinds of cancer, including HCC, have been linked to variations in the TLR4 gene (81). In another study, miRNA499SNPs were shown to decrease the risk of HCC; thus, researchers set out to learn more about the function of miRNAs and the processes by which they contribute to the formation of primary liver cancer (82). The development of HCC is believed to be influenced by various factors, including persistent infections caused by hepatitis B or hepatitis C viruses, exposure to carcinogenic substances, cirrhosis, and multiple SNPs (83).…”
Section: Gene Polymorphismmentioning
confidence: 99%
“…Unfortunately, most HCC patients in Egypt are first diagnosed in the intermediate or advanced stages [1]. For early diagnosis and to reduce HCC-related mortality, new HCC diagnostic and prognostic biomarkers are crucial [2]. Multiple risk factors are correlated with HCC, including alcohol abuse, hepatitis B virus (HBV) or hepatitis C virus (HCV) infection, aflatoxin exposure, nonalcoholic steatohepatitis, and metabolic diseases [2].…”
Section: Introductionmentioning
confidence: 99%